Investigating the use of the e-mail in the teaching and learning of a technical subject among Polytechnic Ungku Omar Students - Chen, Mei Ching (2002)
Through the use of technology in education, effectiveness in the teaching and learning process can be achieved. In this project, the researcher wants to identify whether the usage of the electronic mail in the teaching and learning of a technical subject will benefit the teaching and learning process or not. Other than that, researcher wants to identify problems faced in applying the electronic mail in the teaching and learning of a technical subject among Polytechnic Ungku Omar students. Respondents of the project were one class of Polytechnic Ungku Omar students who were taking Data Communication subject. There were two research approaches used in getting the data which are qualitative approaches and quantitative approach. Qualitative data includes data collected through observations, interview and content analysis. Quantitative data includes data collected through questionnaires. Data collected reveals that participants used the e-mail in different ways which brought them various benefits. E-mail was used as a pedagogy of teaching and learning, medium of communication and tool for different purposes like academic purposes, general query and query for personal development, socializing, complaining and suggesting ideas. The use of e-mail was influenced by factors like gender, personality, experience in using e-mail and the features of the e-mail itself. However, the problem faced by the students such as slow downloading or server problems, limited number of computers for use, limited number of computer labs, many of the computers in the polytechnic were not working properly, crowded computer lab, compact personal time table, lecturer to students ratio was too high, difficult to understand the description, do not have enough money to surf at Cyber Cafe and no free or confirmed access to Internet in Polytechnic have influenced the use of the electronic mail in the teaching and learning of a technical subject among Polytechnic Ungku Omar students